Road Traffic Noise Exposure at Urban Intersections During the Cold Wave: Implications for Public Health in Dhaka, Bangladesh - Majumder, Ahmad Kamruzzaman; Tamanna, Ruhi (International Journal of Health Concord, 2026)
Background: Road traffic noise is an increasingly recognized public health concern in rapidly urbanizing cities, where prolonged exposure may adversely affect physical and mental health. However, evidence on traffic noise exposure during cold-wave conditions in South Asian cities remains limited. This study assessed road traffic noise exposure at urban intersections during the cold wave in Dhaka, Bangladesh, to identify spatial variations and examine their public health implications Methods: A cross-sectional environmental assessment was conducted at 77 road intersections across seven urban zones in Dhaka between January 1 and January 31, 2024. Noise levels were measured three times daily using a standardized sound level meter, and descriptive and spatial analyses were performed to compare noise exposure across different land-use zones Result: The overall mean noise level was 90.29 dBA, substantially exceeding internationally recommended environmental noise limits. The highest mean noise level was recorded in Paltan (105.30 dBA), whereas the lowest was observed at Mintu Road (80.51 dBA). Among the seven study zones, Zone 1 (Ramna) exhibited the highest average noise exposure (92.83 dBA), while Zone 7 (Tejgaon) had the lowest (87.93 dBA). Spatial analysis revealed consistently elevated noise exposure across major traffic intersections, indicating widespread environmental noise burdens throughout the city Conclusion: Road traffic noise exposure during the cold wave was consistently high across urban intersections in Dhaka, suggesting a substantial environmental health burden. These findings highlight the need for strengthened urban noise management strategies and public health interventions to reduce population exposure and support healthier urban environments.